Perception of Employees Regarding the Quality Management System Implemented at a Tertiary Care Eye Hospital in North India: A Mixed-Methods Study. (June 2022) - Dubey, S.; John, D.; Arora, A K; Mathur, Umang; Singh, A K
Background: Quality management in healthcare is critical for hospitals and everyone in the loop —from physicians to support staff—needs to be aware of and involved in this process. Objectives: To assess the perception of employees about the quality management system (QMS) implemented at a tertiary care eye hospital in north India and to use it to identify scope for further improvement. Methods: This cross-sectional mixed-method study involved both questionnaire-based survey and an in-depth interview by a third party. The questionnaire had 12 questions to assess the changes in culture, infrastructure, environment, system, operation theatre and outpatient department. Employees shared their opinion about improvements brought by the QMS in eight years. Respondents were divided into five groups based on their job description: (i) doctors, (ii) technical staff (nursing/operation theatre/laboratory), (iii) optometrists/opticians/audiologists, (iv) patient care executives and (v) human resources/administration/others. Results: Of the 73 employees interviewed, 94.5% perceived an improved treatment and care process and 91.8% perceived improved treatment results. According to 83.6% of the employees, they were encouraged to report patient safety concerns and 71.2% saw improved incidence and adverse event management. The QMS has increased patient satisfaction according to 83%, while 91.8% felt it improved the profile of the hospital. The employees stated no negative effects of the QMS except a long waiting time of the patients and the duplication of paperwork. Conclusion: QMS has brought many positive changes across the hospital. Still, there is scope to reduce the patient waiting time and paperwork duplication.